Die rol van rituele en simbole in die identiteitsvorming van 'n geloofsgemeenskap - 'n Gereformeerde perspektief - Pieterse, Hendrik J. C. (Verbum et ecclesia, 1998)
The role of rituals and symbols in the identity of a faith community - a Reformed perspective The political dispensation in South Africa since 1994 marginalised Afrikaansspeaking Dutch Reformed church members in the new South African society. Their identity is under pressure in a dominant culture that differs from their own. Anxiety and feelings of insecurity about their existence in the future are rife among many people in this church. In this context a new need for religious experiences of identity, belonging and safety opened up new experiments in the liturgy of the church. A new interest in rituals and symbols in the worship service came to the fore. This article discusses a Reformed perspective on the function and meaning of rituals and symbols in liturgy with a view to support the communicative discourse in seeking mutual understanding of the identity of their community offaith in a dominant, different culture.